Amylase activity in various digestive organs and blood urea levels of Osphronemus gouramy with Chlorella vulgaris feed supplementation and reared in different system : Amylase activities and blood urea levels of Osphronemus gouramy - Simanjuntak, Sorta Basar Ida; Wijayanti, Gratiana Ekaningsih; Zuwanda, Maditaningtyas Hawwa; Winarni, Elly Tuti (Journal of Tropical Life Science, 2023)
Osphronemus gouramy is a potential Indonesian fish that needs to be supported by good nutritional feed and water quality in a culture system. The research on the effect of combining Chlorella vulgaris (C. vulgaris) supplementation with culture systems of biofloc and non-biofloc in gourami fish on amylase activity and blood urea level has not been conducted. Therefore, this study aims to determine the effect of C. vulgaris supplementation with different culture systems on the amylase activity of various digestive organs and blood urea levels. It obtains the best C. vulgaris supplementation feed combination to increase the amylase activity of various digestive organs and reduce blood urea levels. This research was carried out experimentally with a Factorial Completely Randomized Design consisting of two factors. Furthermore, gourami was fed with C. vulgaris levels of 0, 2, 3, 4, and 5 g kg-1 for 28 days and divided into biofloc and non-biofloc groups of culture systems. The amylase activity was measured at three pH buffers, and blood urea levels were analyzed using a urea kit. The results showed that amylase activity increased when supplemented with C. vulgaris 5 g kg-1 feed using the biofloc system, while blood urea levels decreased. C. vulgaris supplementation and biofloc system are alternative solutions to improving nutrition and water quality.